Pelaksanaan Pemberian Santunan Pada Korban Kecelakaan Lalu Lintas PT Jasa Raharja Perwakilan Medan - ika annisa annisa; Rahmi Syahriza (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
Implementation in providing compensation (compensation) to victims of traffic accidents at PT Jasa Raharja Representative Medan. This research was conducted to examine and examine how the compensation for traffic accident victims of PT Jasa Raharja Representative Medan, and to find out the obstacles that occurred in the process of submitting traffic accident claims. The method used in this research is qualitative where the data is obtained by conducting interviews and also sourced from the literature. The results of this study indicate that the control in providing compensation for PT Jasa Raharja Representatives of Medan to victims of traffic accidents has been carried out quite well. Judging from the response of employees who judged that the process of providing compensation, policies, and timeliness had been carried out well. PT Jasa Raharja performs its duties in accordance with its commitment to serving traffic accident victims. But there are also obstacles in applying for compensation funds, this is due to the fact that there are still many people who do not understand what are the requirements to apply for compensation, such as a certificate from the police.